2007
DOI: 10.1143/jjap.46.1
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Microcrystalline Cubic Silicon Carbide/Crystalline Silicon Heterojunction Solar Cell by Hot Wire Chemical Vapor Deposition

Abstract: The n-type microcrystalline cubic silicon carbide (mc-3C-SiC:H) films were deposited by hot wire chemical vapor deposition (HWCVD) at a low substrate temperature ($300 C). Heterojunction silicon based photovoltaic devices were fabricated by depositing wide band gap n-type mc-3C-SiC thin films on p-type Si wafers, whose thickness and resistivity were 200 mm and 1-10 cm, respectively. The silicon wafers were textured using alkaline etchant prior to the device fabrication. The photovoltaic parameters of a typical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“… However, the deposition conditions for growing highly transparent μc‐SiC:H(n) on top of a‐Si:H(i) lead to strong deterioration of the underlying amorphous silicon layers, because of etch‐off of the films, , . This trade‐off between high‐quality passivation and attractive transparency has limited the beneficial implementation of μc‐SiC:H(n) in silicon solar cells for a long time. In the past, we showed that it is possible to fabricate symmetric test structures, where the layer stack of HWCVD‐grown μc‐SiC:H(n) on tunnel SiO 2 passivated the c‐Si surfaces.…”
Section: Introductionmentioning
confidence: 99%
“… However, the deposition conditions for growing highly transparent μc‐SiC:H(n) on top of a‐Si:H(i) lead to strong deterioration of the underlying amorphous silicon layers, because of etch‐off of the films, , . This trade‐off between high‐quality passivation and attractive transparency has limited the beneficial implementation of μc‐SiC:H(n) in silicon solar cells for a long time. In the past, we showed that it is possible to fabricate symmetric test structures, where the layer stack of HWCVD‐grown μc‐SiC:H(n) on tunnel SiO 2 passivated the c‐Si surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…5,6) We also reported n-and p-type doping into nc-3C-SiC:H 1,7,8) and the fabrication of heterojunction crystalline silicon solar cells with an n-type nc-3C-SiC:H window layer deposited by HWCVD. The solar cells showed a high quantum efficiency of about 0.8 at a wavelength of 400 nm, reflecting the low optical absorption of nc-3C-SiC:H. 8,9) Although the short circuit current density and fill factor of the solar cells were sufficient, the open circuit voltage is very low to achieve a high conversion efficiency. We also found that the low open circuit voltage was caused by a poor interface between the silicon wafer and the nc-3C-SiC:H window layer.…”
Section: Effects Of Hydrogen Dilution Ratio On Properties Of Hydrogenmentioning
confidence: 96%
“…Besides silicon, HWCVD technique also shows its superiority in depositing stoichiometric microcrystalline silicon carbide (μc-SiC:H) material with mainly cubic SiC polytype at low substrate temperatures [7][8][9][10][11]. Such wide band-gap μc-SiC:H material is an outstanding window layer for solar cells, such as silicon thin film solar cells [12,13] and silicon heterojunction solar cells [14][15][16][17]. In terms of the deposition process, it is of great technical interest and importance to deposit varieties of materials in one processing chamber.…”
Section: Introductionmentioning
confidence: 99%